Short Communication: Serratia rubidaea as contaminant in laboratory environment - Dewi Peti Virgianti (Nusantara Bioscience, 2021)
Abstract. Virgianti DP. 2021. Short Communication: Serratia rubidaea as contaminant in laboratory environment. Nusantara Bioscience 13: 47-51. There have been many cases of bacterial contamination in the laboratory. The bacterial genera identified as contaminants are Bacillus, Staphylococcus, Micrococcus, Pseudomonas, Shigella and Serratia. These bacteria are classified as non-pathogenic and pathogenic bacteria that can interfere with the test and potentially develop false-positive results. The present research has shown that red-colored contaminant bacteria develop in unused sterile media in our laboratory. Based on related information, Serratia marcescens is a red bacterial species that have been reported as a contaminant in the laboratory. The purpose of this study was to identifiy contaminant bacteria at the molecular level. Based on the phylogenetic characterization using the 16S rDNA gene region, this red contaminant bacterium was identified as Serratia rubidaea.